Processo biotecnológico para aproveitamento de soro obtido na produção do queijo de coalho - Meneses, Afram Domingos Silva de (2009)
The whey generated during cheese curd manufacture is a byproduct of great importance for cheese industry. Since a large volume of whey is produced and it is rich in several nutrients, the utilization of this product gains importance. The objective of this work was to develop a biotechnological process for obtaining compounds of higher aggregated values by promoting fermentation of whey from cheese curd manufacture. Several fermentations utilizing whey as a substrate were undertaken by using the yeast kluyveromices lactis in the initial concentrations of 9.0 g/L and 19.0g/L, and with the non-sterilized whey in its natural form as obtained in the process of manufacture of cheese curd. In relation to physico-chemical characteristics, increase in protein and lactose consumption was observed in all the fermentations undertaken and these values were relatively more when yeast concentration used for fermentation was of 9.0 g/L. The microbial growth curves were constructed for all the fermentations and fermented samples withdrawn characterizing each phase (14, 30 and 62 hours of fermentation) were analyzed in a gas chromatographic system coupled with several detectors for the presence of volatile compounds. The results demonstrated that between 200 to 252 volatile constituents were captured by dynamic headspace method, between 141 to 235 by liquid-liquid extraction and between 149 to 301 by simultaneous distillation and extraction method. In the volatiles extracted from different fermented products, the presence of compounds such as 2-hexadecenal, octadecanoico acid, hexadecanamide, 3-hexenol was revealed and these are relatively costly compounds as their market price varies from 70.06 to 194.50 US$/100 mL. It could be concluded from the results obtained in this study that the whey fermentation by usage of kluyveromices lactis is a promising biotechnological process for obtaining volatile compounds of higher commercial values.